PENGOPTIMALAN DALAM PENGEMBANGAN PROGRAM MAGGOT RAMAH LINGKUNGAN UNTUK KESEJAHTERAAN BERKELANJUTAN DI DESA SUGIAN, KECAMATAN SAMBELIA, KABUPATEN LOMBOK TIMUR - Muktadir, Neil; Jurnal Wicara; Jayaprana, Dodik; Pratama, Sendi; Cahyani, Kurnia; Misfala; Nugraha, Mahardika; Maulidiawati, Ria; Khaliza, Rizma; Angelina, Alifia; Muhlis (Universitas Mataram, 2025)
The organic waste management program based on Black Soldier Fly (BSF) maggot cultivation has been implemented as an innovative solution to reduce waste generation and provide alternative livestock feed in Sugian Village. The method applied was Community Based Research (CBR), actively involving the community from the planning to the implementation stages. Activities included socialization, training on media preparation, daily maintenance, and mentoring for independent cultivation trials. The results indicated a significant increase in community knowledge and skills, particularly in media preparation techniques, organic feed selection, moisture control, and maggot harvesting. Furthermore, residents have begun diverting household organic waste to maggot cultivation media, although the waste reduction scale remains limited at the early stage. This program has proven to deliver ecological benefits by reducing organic waste volume, economic benefits by providing high-quality livestock feed at a lower cost, and social benefits by strengthening collaboration among residents, environmental groups, and academics.